Pengaruh Pemberian Agen Kontras Pewarna Sintetik pada Jaringan Biologis terhadap Hasil Pencitraan Fotoakustik - Janna, Miftahul; Mitrayana, Mitrayana; Widyaningrum, Rini (Department of Physics, Sebelas Maret University, 2022)
An experiment to investigate the influence of synthetic dye contrast agent in photoacoustic imaging of biological tissue was conducted in this study. This study uses a simple phocoacoustic imaging system consists of three main components, i.e., a diode laser, condenser microphone, and a custom-build X-Y stage. Characterization was performed on the main components of the system to obtain the appropriate settings on imaging the biological tissue in this study. The results of the optimal frequency and duty cycle for laser modulation in this study were 19000 Hz and duty cyle of 40%, respectively. The addition of a contrast agent aims to improve the quality of the image by comparing the sample with methylene blue contrast agent, the sample with methyl red and the sample without contrast agent. The increases of acoustic intensity level is in proportion with the contrast agent concentration. The difference in the photoacoustic images reveal that the sample with methylene blue contrast agent has the highest acoustic intensity level compared to both sample with methyl red contrast agent and the sample without contrast agent. Therefore, this research proves that a photoacoustic imaging system can be developed to image biological tissue with a contrast agent and methylene blue has greater potential than methyl red to be used as a contrast agent in photoacoustic imaging.